EFFECTIVITY OF THE CONSUMERISM EDUCATION VIDEO ON DECREASING THE CONSUMPTIVE BEHAVIOR - Kusuma Putri, Sheren Regina; Annisa Maula; Trie Andini k; Azzahra Amelia Putri; Deska Fitria (CV. Era Digital Nusantara, 2022)
This study aims to see the effectiveness of consumerism educational videos in reducing consumptive behavior. The research method used is a quantitative method with an experimental type of research, and researchers use a one group pretest design – posttest design. The population in this study were female students of Psychology Faculty In Raden Fatah State Islamic University, and researchers used purposive sampling techniques to select samples. The study used a questionnaire that refers to the theory of Consumptive Behavior by Lina and Rosyid, which consists of Impulsive Buying, Wasteful Buying, and Non – Rational Buying. The questionnaire was distributed to 30 people who had a fairly high shopping intensity with 28 valid items with an items correlation index between 0.292 – 0.743. Test the hypothesis used in this study by utilizing the paired sample t – test technique calculated using SPSS 22.0 for windows with the results of the t-test hypothesis – test which shows that there are significant changes that occur between the pretest and the posttest. From the results of the study, it shows that the provision of consumerism educational video treatment has an influence in reducing the consumptive behavior of female students, and the hypothesis is stated to be accepted.